Architecture of Peace in Ambon: Reading Dynamics of Peace After Ten Years of Conflict - Saidin Ernas (Al-Albab, 2016)
The dynamics of peace in Ambon have been getting stronger during the last ten years, but to what extent this phenomenon can be considered as a solid basis for peace, would require a critical analysis. This paper is the result of field research on peace in Ambon using the theory of "peace architecture" developed by Luc Reychland (2006). The results of the analysis obtained several important conclusions. First, the peace process in the city of Ambon has been going on in a participatory manner in various aspects of life. Second, in an architectural perspective as put forward by Reychland, the peace in Ambon has sufficient potential to develop into a structure of peace which is getting stronger. It is characterized by the strengthening of an increasingly inclusive dialog and communication between citizens, as well as the effectiveness of public arenas such as markets, offices, schools and coffee shops as a medium of integration. It is also supported by the accommodative practices of economic and political transformation. Third, in line with the positive development, the public still need to be reminded of radical religious ideas and identity politics that are harmful to the sustainability of peace.